RADIATION EXPOSURE PROFILE IN RADIOLOGICAL DEPARTMENT TO SUPPORTING PROTECTION PROGRAMS IN HOSPITALS / RADIOLOGICAL CLINIC LABORATORY IN SEMARANG CITY - Dwi Rochmayanti; Siti Daryati; Darmini Darmini; Yeti Kartikasari (Poltekkes Kemenkes Semarang, 2019)
Background: All acts of radiation use, both for diagnostics, therapy and nuclear medicine, must go through a process of justification, limitation and optimization so that patients, officers and the surrounding environment get as much diagnostic benefit as possible with the smallest possible radiation risk. Some problems that arise in the Hospital / clinic, often ignore and do not pay attention to work exposure safety factors. The purpose of this study was to determine the profile of occupational radiation exposure and the effectiveness of radiation shielding in the radiology department of the Semarang city then compared to the reference dose to determine the optimization of radiation protection.Methods: The type of research conducted is quantitative research with a survey and observational approach. Exposure measurements were carried out in 5 radiology department, which included 3 hospitals and 2 clinical laboratories. Documents and room observations are also carried out. For the effectiveness of the radiation barrier it is also measured before and after the radiation shielding by using a surveymeter tool. The results data are then presented in descriptive analyses.Results: The results of the study of radiation exposure profiles in five radiology institutions, four institutions there was radiation exposure recorded on the surveymeter tool, with the largest exposure value was 0.099 mSv / h (still below the safe limit of 1 mSv / year). Only one hospital is safe, and there are no leaks.Conclusions: The effectiveness of the radiation retaining wall, four hospitals have a barrier level equal to 1 mm Pb at 80 kVp irradiation, and 1 hospital (RSJ) has a radiation barrier equivalent to 0.5 mmPb.